2019
DOI: 10.1093/ecco-jcc/jjz001
|View full text |Cite
|
Sign up to set email alerts
|

The Adipokine Metrnl Ameliorates Chronic Colitis in Il-10–/– Mice by Attenuating Mesenteric Adipose Tissue Lesions During Spontaneous Colitis

Abstract: Background Crosstalk between mesenteric adipose tissue [MAT] and the intestines affects the progression of Crohn’s disease [CD]. The adipokine metrnl regulates adipocyte function and has anti-inflammatory activity. We aimed to explore metrnl expression in CD MAT, investigate the influence of metrnl on the experimental colitis disease course and determine the mechanism underlying this effect. Methods Metrnl expression in MAT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…This adipo-myokine is induced in skeletal muscle upon cold exposure, and this peptide has been shown to exert an anti-inflammatory activity due to an increase in beige fat thermogenesis [161,162]. Metrnl expression is higher in mWAT of CD patients in comparison to the controls [163].…”
Section: Other Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…This adipo-myokine is induced in skeletal muscle upon cold exposure, and this peptide has been shown to exert an anti-inflammatory activity due to an increase in beige fat thermogenesis [161,162]. Metrnl expression is higher in mWAT of CD patients in comparison to the controls [163].…”
Section: Other Adipokinesmentioning
confidence: 99%
“…Zuo et al [163] 2019 Spontaneously developing chronic colitis in IL-10 −/− mice In IL-10 −/− mice with spontaneous colitis, administration of metrnl decreases pathological alterations in mWAT, increases adipocyte size, and ameliorates inflammation.…”
Section: Year Study Type Conclusionmentioning
confidence: 99%
“…Therefore, they suggested that, upregulation of Metrnl in the MAT of the patients may be a compensatory response [14]. Regarding the inconvenient results, it seems likely that, Metrnl expression can have an organ dependent pattern; however, further longitudinal research is needed to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meteorin-like (Metrnl, known as Subfatin) is a novel adipo-myokine that is mainly expressed in WAT, however, it was also reported that Metrnl is expressed colon epithelium. The anti-in ammatory function of Metrnl has been revealed recently [14]. Moreover, it can enhance lipid metabolism, decrease adipose in ammation, and ameliorate obesity-mediated insulin resistance (IR).…”
Section: Introductionmentioning
confidence: 99%
“…Meteorin-like (Metrnl, known as Subfatin) is a novel adipo-myokine that is mainly expressed in WAT, however, it was reported that Metrnl is also expressed in colon epithelium. The anti-in ammatory function of Metrnl has been revealed recently and also has other roles including enhancing lipid metabolism, decreasing adipose in ammation, and ameliorating obesity-mediated insulin resistance (IR) [14]. Notably, Metrnl expression was higher in mesenteric WAT of the CD patients in comparison to the controls [15] .…”
Section: Introductionmentioning
confidence: 99%